Optimizing Sustainability in Bridge Projects: A Framework Integrating Risk Analysis and BIM with LCSA According to ISO Standards - Dema Munef Ahmad; László Gáspár; Rana Ahmad Maya (Applied Sciences)
Building bridges sustainably is essential for advancing infrastructure development and ensuring long-term environmental, social, and economic viability. This study presents a framework that integrates risk management strategies and Building Information Modeling (BIM) with Life Cycle Sustainability Assessment (LCSA) standards to enhance bridge project sustainability. Through a targeted survey, the study evaluates risks across bridge lifecycle phases, identifying the main processes that significantly impact sustainability. Using the Pareto Principle, the framework prioritizes these processes and associated risks, guiding the creation of targeted improvement guidelines aligned with ISO 9001:2015, BIM, and LCSA standards, which support high quality and efficiency. The results reveal that 38 of 55 identified risks account for 80% of the lifecycle impact, and they include the majority of those derived from international standards, underscoring their significance in sustainability efforts. Additionally, 36 of 47 main processes are subject to 80% of the impact from these vital risks, highlighting phases like Construction and Supervision as priority areas for intervention. By linking specific risks to each process within these phases, the study outlines essential guidelines and strategic measures, ensuring a focused approach to sustainable bridge development that aligns with international standards and maximizes lifecycle sustainability outcomes.